2017
DOI: 10.1063/1.4973828
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent fluctuations during pellet injection into a dipole confined plasma torus

Abstract: We report measurements of the turbulent evolution of the plasma density profile following the fast injection of lithium pellets into the Levitated Dipole Experiment (LDX) [Boxer et al., Nat. Phys. 6, 207 (2010)]. As the pellet passes through the plasma, it provides a significant internal particle source and allows investigation of density profile evolution, turbulent relaxation, and turbulent fluctuations. The total electron number within the dipole plasma torus increases by more than a factor of three, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
3
8
0
Order By: Relevance
“…Similar phenomena have been observed in the CTX [12] and the LDX [8] as interchange and entropy modes. In the CTX, it has been reported that the instantaneous particle transport is intermittent, and the detailed time evolutions of the perturbed flux-tube number and potential indicate that convective transport dominates in the dipole configuration.…”
Section: Discussion and Summarysupporting
confidence: 80%
See 1 more Smart Citation
“…Similar phenomena have been observed in the CTX [12] and the LDX [8] as interchange and entropy modes. In the CTX, it has been reported that the instantaneous particle transport is intermittent, and the detailed time evolutions of the perturbed flux-tube number and potential indicate that convective transport dominates in the dipole configuration.…”
Section: Discussion and Summarysupporting
confidence: 80%
“…The fluctuation level increases obviously near the cut-off density, suggesting the density dependence of the fluctuations. The particle transport characterizes a turbulent diffusion driven by the electric-field fluctuations which are related to the presence of entropy modes observed in a laboratory magnetospheric plasma of the LDX [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical and experimental results in Refs. [3][4][5] show that the dipole confinement is good even under the stochastic motion of particles due to the collision and turbulence, at least under the present laboratory low temperature and density parameters. However, the confinement properties of dipole field under fusion parameters, e.g., high temperature and density and the gradient of them, are still open questions.…”
Section: Introductionmentioning
confidence: 63%
“…Dipole magnetic fields widely exist in the Universe, such as in the planetary magnetospheres. The idea of using strong dipole field configuration for magnetic confinement of laboratory plasmas for fusion is proposed theoretically by Hasegawa [1,2] and several experimental devices have also been built since then, such as the Levitated Dipole Experiment (LDX) [3][4][5] at MIT, the Collisionless Terrella Experiment (CTX) [6] at Columbia University and Ring Trap-1 (RT-1) [7,8] at the University of Tokyo. The dipole configuration is also used to confine electron-positron pair plasmas in the laboratory [9].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis effectively restricts the applicability of the HM equation to plasmas with a small density gradient and to magnetic fields with small curvature or field inhomogeneities. However, experimental observations pertaining to plasmas confined by dipole magnetic fields [16,17] suggest the existence of drift wave turbulence and zonal flows in systems where both the electron spatial density and the magnetic field are characterized by strong gradients over spatial scales comparable to that of electric field and density fluctuations (these low frequency fluctuations are often referred to as entropy modes [18]). In principle, an accurate description of electromagnetic turbulence in such setting could be obtained with the aid of nonlinear gyrokinetic theory [19,20,21].…”
Section: Introductionmentioning
confidence: 99%